2011
DOI: 10.1161/circulationaha.110.010736
|View full text |Cite
|
Sign up to set email alerts
|

Perishock Pause

Abstract: BACKGROUND Peri-shock pauses are pauses in chest compressions prior to and following defibrillatory shock. We examined the relationship between peri-shock pauses and survival to hospital discharge. METHODS We included out-of-hospital cardiac arrest (OHCA) patients in the Resuscitation Outcomes Consortium Epistry-Cardiac Arrest who suffered arrest between December 2005 and June 2007, presented with a shockable rhythm (ventricular fibrillation or pulseless ventricular tachycardia) and had CPR process data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 323 publications
(111 citation statements)
references
References 30 publications
3
104
2
2
Order By: Relevance
“…There was a general improvement in CPR quality by cardiac arrest teams across all hospital sites. Some statistically significant improvements were observed, but the effect size of these improvements were small and their influence on clinical outcomes uncertain.. [21,24,25] The study found no evidence that interventions were associated with an effect on patient outcome, but the study was not powered to detect such differences.…”
Section: Discussionmentioning
confidence: 99%
“…There was a general improvement in CPR quality by cardiac arrest teams across all hospital sites. Some statistically significant improvements were observed, but the effect size of these improvements were small and their influence on clinical outcomes uncertain.. [21,24,25] The study found no evidence that interventions were associated with an effect on patient outcome, but the study was not powered to detect such differences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in human case reports, it was observed that switching from mCPR to manual compressions enabled increasing chest compression depth, resulting in hemodynamic improvement, which highlighted the usefulness of physiological monitoring during CPR 50. There is clinical evidence to support that the assessment of CPR quality has revealed significant increases in survival and a favorable neurological function after cardiac arrest 51, 52. Thus, it is possible that the use of mCPR with an assessment of CPR quality may be useful to improve the resuscitation performance.…”
Section: Discussionmentioning
confidence: 99%
“…With every 5-second increase in pre-and peri-shock pause, the probability of survival was reduced by 18% and 14%, respectively. 18,19 These components of CPR quality are not only highlighted as benchmarks for prehospital resuscitation, but also are increasingly becoming standards to which in-hospital resuscitation should strive. In an attempt to improve adherence to evidence-based care of patients who sustain cardiac arrest, the AHA developed a quality improvement program known as Get with the Guidelines-Resuscitation.…”
Section: Peri-shock Pausementioning
confidence: 99%